Pengaruh Current Ratio, Debt To Equity Ratio, Total Asset Turnover, Terhadap Return On Asset Pada Perusahaan Tambang Logam Yang Terdaftar di BEI Tahun 2019-2024 - Rivadilla Natasha; Ferry Kosadi (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This research looks at how financial performance ratios affect ROA in metal mining companies listed on the IDX between 2019 and 2024. The study employs a quantitative approach, using descriptive and verificatory methods and secondary data from annual financial reports. A purposive sampling approach was used to select six companies, yielding 30 observations. The data was analyzed using multiple linear regression, t-tests, F-tests, descriptive statistics, and traditional assumption tests. The findings show that ROA is strongly and adversely impacted by the DER, indicating that higher leverage reduces profitability. Conversely, the CR and TATO have a positive and significant influence on ROA. ROA is significantly affected by all independent components, underscoring the importance of capital structure, efficiency, and liquidity in decision-making.